A Quantitative Analysis of Open Access in Digital Humanities Journals - Martínez Cantón, Clara Isabel (Revista General de Información y Documentación, 2021)
This paper presents a study of open access in a corpus of Digital Humanities journals selected under strict criteria. The main objective of this work is to provide a reliable picture of Digital Humanities periodical academic publishing, with the focus on openness of its publications and its relationship with other dimensions, such as journal provenance, type of publisher, languages of publication, etc. and listing other characteristics such as publication visibility (DOAJ, SHERPA/RoMEO, and SCOPUS), years in publication, publication charges and embargo period.The study, carried out on a corpus of 38 selected journals of the discipline, reveals that Digital Humanities journals are mostly inclined to open access at its highest level. Only one of them does not allow any type of open access, while 7 of them are hybrid (green route if authors do not pay, gold route if they pay fees), one is gold open access and the remaining 29 are diamond open access. In other words, 76.3% of the journals in the corpus are platinum/diamond open access, at no cost to authors or readers. In them, publication costs are covered by grants, free software, voluntary work, etc. This study aims to visualize the position of publications in the field of Digital Humanities at a time when Open Science is revolutionizing the paradigm of scientific communication.
Keywords: Digital Humanities; Academic Journals; Open Access; Scholarly Journals; Open Science